Peningkatan Kompetensi Guru Melalui Kegiatan Pelatihan Dan Pendampingan Penyusunan Karya Ilmiah Bagi Guru- Guru SMAN 5 Taruna Brawijaya Kediri - Sopiah Sopiah; Handri Dian Wahyudi; Fitriana Fitriana; Etta Mamang Sangadji (Fakultas Teknik Universitas Cenderawasih, 2023)
Improving teacher competence in the preparation of scientific work is very important. Apart from the fact that teachers are required by regulations to compile scientific work every year at least once, being a competent/professional teacher is a necessity. This PKM aims to improve teacher competence through training activities and mentoring in the preparation of scientific work. The PKM method used is a service learning process: Investigation, Preparation, Action, and Reflection (Pramanik et al., 2021). The subjects of the dedication were the teachers of SMAN 5 Taruna Brawijaya Kediri. Retrieval of data using interviews, observations, tests and questionnaires. The results of PKM activities show an increase in teacher competence in the preparation of scientific work (preparation of research proposals, preparation of research reports, preparation of research outputs, preparation of teaching materials (books/modules/student worksheets) before and after PKM activities. Participant responses to PKM activities were positive and meaningful and they recommend similar activities in the future.